The effectiveness of gluten-free dietary interventions: A systematic review - Poslt Königová, Michaela; Sebalo Vňuková, Martina; Řehořková, Petra; Anders, Martin; Ptáček, Radek (Frontiers in Psychology, 2023)
Celiac disease is a chronic autoimmune gastroenterological disorder in which the digestion of gluten leads to damage and constant inflammation in the small intestine. Moreover, there are associated physical and mental health problems related to celiac disease, i.e., a lower health-related quality of life and increased depression and anxiety symptoms. The only effective treatment for celiac disease is lifelong adherence to a gluten-free diet. However, researchers suggest that strict adherence to a gluten-free diet ranges from 42 to 80%, depending on the definition and method of assessment that was utilized. This review examines interventions designed for those who need to adhere to life-long dietary measures and their success in terms of increasing gluten-free dietary adherence and improving their health-related quality of life. In April 2022, the Scopus, Web of Science, PubMed and ProQuest databases were searched using the following terms: “coeliac disease” OR “celiac disease” AND “gluten free diet” AND “intervention” AND “health related quality of life” AND “diabetes.” Eight studies were suitable for this review. The studies were used to analyze different intervention techniques and their impact on gluten-free dietary adherence, quality of life, and the reasons for dietary nonadherence. The studies revealed statistically significant improvements in the knowledge base regarding celiac disease and the gluten-free diet, dietary adherence and quality-of-life satisfaction immediately after the intervention and at a three-month follow-up. Some studies were also focused on behavioral and cognitive aspects of nonadherence to dietary measures.